2015
DOI: 10.1002/pca.2578
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation of triterpenes and phenolic compounds in australian Centella asiatica (L.) Urb

Abstract: The results indicate that harvesting C. asiatica in summer returns the highest yield of the target triterpenoids, kaempferol and chlorogenic acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
44
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(60 citation statements)
references
References 24 publications
8
44
1
1
Order By: Relevance
“…Similar studies have been reported on C. asiatica wherein it was shown to accumulate major phytoconstituents in the months of summer season (Alqahtani et al, 2015). Moreover, studies on Ribes nigrum and 'Zonouz' peel have shown that harvesting time and leaf position have a profound effect on their phenolic contents and (Michael et al, 2015 andHallman et al, 2013).…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…Similar studies have been reported on C. asiatica wherein it was shown to accumulate major phytoconstituents in the months of summer season (Alqahtani et al, 2015). Moreover, studies on Ribes nigrum and 'Zonouz' peel have shown that harvesting time and leaf position have a profound effect on their phenolic contents and (Michael et al, 2015 andHallman et al, 2013).…”
Section: Resultssupporting
confidence: 63%
“…A wide range of chemical compounds including cardiac glycosides, fl avonoids, terpenoids, alkaloids and resins have been isolated from this plant (Singh et al 2014). Recent studies have shown that, C. asiatica accumulates major phytoconstituents in the months of summer season (Alqahtani et al, 2015). Moreover, studies on Ribes nigrum and 'Zonouz' peel have shown that harvesting time and leaf position have a profound effect on their phenolic contents, (Hallman et al, 2013 andMichael et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This extract contains a high proportion of glycosides than the aglycones, in which madecassoside is the highest component. Several researchers were able to detect these triterpenes within the wavelength range of 200-220 using a gradient system comprising water and acetonitrile [28][29][30]. The cytotoxic effect of RECA at a concentration ranging from 3.91 to 1000 µg/mL was investigated on neuroblastoma cells (SH-SY5Y) and murine microglia cells (RAW 264.7) by using MTT assay.…”
Section: Quantitative High-performance Liquid Chromatography (Hplc) Amentioning
confidence: 99%
“…Then the sample solution was filtered through a 0.45‐μm syringe filter, and 10 μL of the filtrate was injected into the HPLC system for quantification analysis. The quantitation of each compound was expressed as grams per 100 grams of dried weight (g/100 g DW) of the seed shell …”
Section: Methodsmentioning
confidence: 99%